ORGANISATIONAL MANAGEMENT TRANSFORMATION STRATEGIES IN HEALTHCARE SERVICES: A LITERATURE REVIEW ON INFORMATION SYSTEM INTEGRATION, HUMAN RESOURCE PERFORMANCE IMPROVEMENT, AND SERVICE QUALITY OPTIMISATION FOR PATIENTS IN THE DIGITAL AGE - B.M.A.S. Anaconda Bangkara; Raba Nathaniel; Rudianto (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
Organisational management transformation in healthcare services is a strategic necessity in the digital age, which is characterised by advances in information technology and increasing patient expectations regarding service quality. This study aims to analyse healthcare organisational management transformation strategies through a literature review of three main aspects, namely information system integration, human resource performance improvement, and patient service quality optimisation. The method used is a systematic literature review with scientific data sources from international databases such as Scopus, PubMed, and ScienceDirect. The results show that information system integration, whether in the form of Electronic Health Records, Hospital Information Systems, or telemedicine, can improve managerial efficiency and data-based decision-making. However, the success of this digital transformation is highly dependent on the readiness and competence of human resources who are responsive to technological changes and have high digital literacy. Improving human resource performance through continuous training, transformational leadership, and an innovative organisational culture has been proven to have a significant effect on service quality and patient satisfaction. Overall, an effective management transformation strategy must integrate technology and people into a harmonious value system to create resilient, efficient, and patient-oriented healthcare services in the digital era.